A comprehensive preimplantation genetic testing approach for SEA-type α-thalassemia by fluorescent gap-polymerase chain reaction combined with haplotype analysis - Wang, Jing; Ma, Yuanlin; Guo, Jing; Li, Rong; Zhou, Canquan; Xu, Yanwen (Frontiers in Genetics, 2023)
Introduction: This study aimed to evaluate the feasibility and necessity of using fluorescence Gap-polymerase chain reaction combined with haplotype analysis in preimplantation genetic testing for SEA-type α-thalassemia. Methods: A total of 26 preimplantation genetic testing biopsy cycles were performed in 25 families from June 2021 to February 2022. All couples were carriers of SEA-type α-thalassemia. Fluorescent Gap-polymerase chain reaction was used for detecting fragment deletion. Subsequently, according to the results of polymerase chain reaction, reference embryos were identified to establish haplotype using single nucleotide polymorphism array, and aneuploidy was screened simultaneously. In cases wherein the polymerase chain reaction results were inconsistent with the haplotype results, the reasons were investigated, either by retest of the biopsied samples or rebiopsy of the embryo. Results: Among the 172 embryos, 162 had consistent results when tested using both methods, resulting in a consistency rate of 94.2%. Conversely, 10 embryos had inconsistent results, mainly due to chromosome 16 aneuploidy (n = 7), allele dropout in Gap-polymerase chain reaction (n = 2), or incorrect haplotype due to poor sample amplification quality (n = 1). The clinical pregnancy rate of each frozen-thawed embryo transfer was 57.7% (15/26). Six families underwent prenatal diagnosis, which confirmed the results of preimplantation genetic testing. Conclusion: Fluorescent Gap-polymerase chain reaction combined with haplotype analysis is feasible and necessary for SEA-type α-thalassemia preimplantation genetic testing.